2021
DOI: 10.1021/acsami.1c06274
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conductive Cellulose Mats by Solution Blow Spinning as Substrate and a Dielectric Interstrate Layer for Flexible Electronics

Abstract: Renewable cellulose substrates with submicron- and nanoscale structures have revived interest in paper electronics. However, the processes behind their production are still complex and time- and energy-consuming. Besides, the weak electrolytic properties of cellulose with submicron- and nanoscale structures have hindered its application in transistors and integrated circuits with low-voltage operation. Here, we report a simple, low-cost approach to produce flexible ionic conductive cellulose mats using solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Zinc oxide ultraviolet (ZnO UV) sensors were produced to validate the LIGE approach proposed in this study. It is worth noting that ZnO UV sensors have been widely used to identify UV radiation, which is harmful to human health, causing countless cases of skin cancer. , This study collaborates to establish nanocellulose as a precursor material for LIGE, thus may open the way for a new generation for organic electronics, considering that micro- and nanocellulose use has already been established as a substrate and dielectric material in several electronic components. …”
Section: Introductionmentioning
confidence: 90%
“…Zinc oxide ultraviolet (ZnO UV) sensors were produced to validate the LIGE approach proposed in this study. It is worth noting that ZnO UV sensors have been widely used to identify UV radiation, which is harmful to human health, causing countless cases of skin cancer. , This study collaborates to establish nanocellulose as a precursor material for LIGE, thus may open the way for a new generation for organic electronics, considering that micro- and nanocellulose use has already been established as a substrate and dielectric material in several electronic components. …”
Section: Introductionmentioning
confidence: 90%
“…Thus, thinking of it as part of “green” electronic devices in the future is a legitimate aspiration. Solid steps were taken during the last decade with the advent of a range of electronic or electrochemical devices manufactured directly onto paper substrates or from cellulose-based functional materials. , Some examples are biosensors, energy storage, and conversion devices, or even crucial electronic building blocks such as diodes or field-effect transistors (FETs), demonstrating that the paper electronics era is establishing its foundations. ,, …”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 Some examples are biosensors, energy storage, and conversion devices, or even crucial electronic building blocks such as diodes or field-effect transistors (FETs), demonstrating that the paper electronics era is establishing its foundations. 3 , 8 , 10 14 …”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] For instance, an appealing combination of natural and biocompatible materials such as paper, starch, ethylcellulose and nanoparticle-based ink was demonstrated to fabricate all-printed EGTs that can be possibly transferred to any surface of interest. 5,[30][31][32] Regarding surface engineering, single-molecule detection has been demonstrated by functionalizing the gate terminal with specific antibodies able to detect antigens present in the serum. 33 Another brilliant example is the use of the so-termed extended floating gate architecture introduced by Frisbie et al, who demonstrated the importance of controlling the area of the gate terminal coupled with an additional floating gate to endow EGTs with improved sensing capabilities towards ricin protein.…”
Section: Introductionmentioning
confidence: 99%